2005
DOI: 10.1074/jbc.m500943200
|View full text |Cite
|
Sign up to set email alerts
|

Active Site Aspartate Residues Are Critical for Tryptophan Tryptophylquinone Biogenesis in Methylamine Dehydrogenase

Abstract: The biosynthesis of methylamine dehydrogenase (MADH) requires formation of six intrasubunit disulfide bonds, incorporation of two oxygens into residue ␤Trp 57 and covalent cross-linking of ␤Trp 57 to ␤Trp 108 to form the protein-derived cofactor tryptophan tryptophylquinone (TTQ). Residues ␤Asp 76 and ␤Asp 32 are located in close proximity to the quinone oxygens of TTQ in the enzyme active site. These residues are structurally conserved in quinohemoprotein amine dehydrogenase, which possesses a cysteine trypto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…Furthermore, it has been reported that mutation of the non-oxygenated TTQ partner, ␤Trp-108, into Cys leads to the generation of CTQ instead of TTQ in MADH (26), strongly suggesting that biogenesis of TTQ and CTQ shares the common mechanisms at least partly, proceeding within the periplasm. Finally, it is also interesting to note that the mauD gene required for MADH maturation codes for a protein similar to disulfide isomerase that may be involved in the periplasmic processing of the six disulfide bonds of the ␤-subunit of MADH (38), which likely provides a proper positioning of active-site residues involved in TTQ biogenesis (29). Although the ␥-subunit of QHNDH does not contain disulfide bonds, it does contain three Cysto-Asp/Glu thioether cross-links that appear functionally equivalent to disulfide bonds.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been reported that mutation of the non-oxygenated TTQ partner, ␤Trp-108, into Cys leads to the generation of CTQ instead of TTQ in MADH (26), strongly suggesting that biogenesis of TTQ and CTQ shares the common mechanisms at least partly, proceeding within the periplasm. Finally, it is also interesting to note that the mauD gene required for MADH maturation codes for a protein similar to disulfide isomerase that may be involved in the periplasmic processing of the six disulfide bonds of the ␤-subunit of MADH (38), which likely provides a proper positioning of active-site residues involved in TTQ biogenesis (29). Although the ␥-subunit of QHNDH does not contain disulfide bonds, it does contain three Cysto-Asp/Glu thioether cross-links that appear functionally equivalent to disulfide bonds.…”
Section: Discussionmentioning
confidence: 99%
“…A similar effect was reported when the structurally analogous Asp was mutated in methylamine dehydrogenase (MADH). That led to expression of a precursor of MADH without TTQ [10]. …”
Section: Introductionmentioning
confidence: 99%
“…Two other quinoproteins, the CTQ-containing quinohemoprotein amine dehydrogenase (QHNDH) [12] and the TTQ-containing MADH [13], have a structurally conserved Asp residue in the position corresponding to Cys448 in the LodA structure in the active site. Mutation of the corresponding Asp in MADH affected the efficiency of MauG-dependent TTQ biosynthesis but had no effect on the catalytic activity of the population of the isolated MADH with fully formed TTQ [10]. As such, Cys448 in LodA was converted to Asp, as well as Ala, to ascertain its role in CTQ biosynthesis or catalysis or both.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] According to CTQ, putative iron sulfur cluster binding protein probably belongs to the Radical SAM superfamily and can be involved in the biogenesis of QHAmDH, 11) but the details remain obscure. If sQHAmDH is the precursor of QH-AmDH, sQH-AmDH might become a key protein in understanding the biogenesis of post-transcriptionally derived quinone cofactors.…”
Section: Resultsmentioning
confidence: 99%
“…11) In TTQ biosynthesis, MauG protein, an oxygen-binding diheme c protein, would be involved in cross-linking reaction of the two tryptophans. [12][13][14] The largest subunit of QH-AmDH is a 489-residue, a four-domain polypeptide chain that contains two heme c cofactors. Heme c(a) is solvent-accessible and has His and Met as axial ligands.…”
mentioning
confidence: 99%